2006
DOI: 10.3354/meps307273
|View full text |Cite
|
Sign up to set email alerts
|

Lipid storage in marine zooplankton

Abstract: Zooplankton storage lipids play an important role during reproduction, food scarcity, ontogeny and diapause, as shown by studies in various oceanic regions. While triacylglycerols, the primary storage lipid of terrestrial animals, are found in almost all zooplankton species, wax esters are the dominant storage lipid in many deep-living and polar zooplankton taxa. Phospholipids and diacylglycerol ethers are the unique storage lipids used by polar euphausiids and pteropods, respectively. In zooplankton with larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
569
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 648 publications
(593 citation statements)
references
References 290 publications
14
569
2
8
Order By: Relevance
“…The life history pattern of N. cristatus is almost identical everywhere in the subarctic North Pacific Ocean despite the environmental differences (Tsuda et al, 2004). It has been generally accepted that substantial storage of wax esters with long-chain monounsaturated moieties is an adaptation to a pronounced seasonality of food supply (Lee et al, 2006). This lipid accumulation mode of N. cristatus supports the copepod to maintain the stable life history patterns that do not depend on the environmental changes widespread in the subarctic North Pacific Ocean.…”
Section: Neocalanus Cristatusmentioning
confidence: 80%
See 3 more Smart Citations
“…The life history pattern of N. cristatus is almost identical everywhere in the subarctic North Pacific Ocean despite the environmental differences (Tsuda et al, 2004). It has been generally accepted that substantial storage of wax esters with long-chain monounsaturated moieties is an adaptation to a pronounced seasonality of food supply (Lee et al, 2006). This lipid accumulation mode of N. cristatus supports the copepod to maintain the stable life history patterns that do not depend on the environmental changes widespread in the subarctic North Pacific Ocean.…”
Section: Neocalanus Cristatusmentioning
confidence: 80%
“…The long-term lipid deposits are stored as wax esters in many boreal and deep-living zooplankton species (Lee et al, 2006). The wax ester storage is especially pronounced in herbivorous zooplankton and related to the fatty acid and alcohol compositions, i.e., the biosynthesis and accumulation of the 20:1 and 22:1 moieties exclusively produced by herbivorous calanoid copepods (Kattner and Krause, 1989;Kattner and Hagen, 1995;Falk-Petersen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WE: Wax esters (WE) are important and frequently occurring storage lipids in many pelagic crustaceans including euphausiids Saether et al, 1986). It has also been suggested that they play an important role as a 'long-term' lipid store in deep sea and high-latitude zooplankton (Lee et al, 2006). However, only small amounts of WE have been detected in M. norvegica (Fig.…”
Section: Tagmentioning
confidence: 99%